2015
DOI: 10.1038/npjqi.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

Engineering coherent interactions in molecular nanomagnet dimers

Abstract: Proposals for systems embodying condensed matter spin qubits cover a very wide range of length scales, from atomic defects in semiconductors all the way to micron-sized lithographically defined structures. Intermediate scale molecular components exhibit advantages of both limits: like atomic defects, large numbers of identical components can be fabricated; as for lithographically defined structures, each component can be tailored to optimise properties such as quantum coherence. Here we demonstrate what is per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 39 publications
0
98
0
Order By: Relevance
“…This has to be strong enough to obtain a gate time shorter than the phase memory time of qubits, otherwise the information will be lost through decoherence. However, it cannot be too strong, otherwise the gate time would be shorter than the time needed to manipulate a single spin-in pulsed EPR spectroscopy this time is around 10 ns [41].…”
Section: Dimeric Assemblies Of {Cr 7 Ni} Wheels As Double Qubit-basedmentioning
confidence: 99%
“…This has to be strong enough to obtain a gate time shorter than the phase memory time of qubits, otherwise the information will be lost through decoherence. However, it cannot be too strong, otherwise the gate time would be shorter than the time needed to manipulate a single spin-in pulsed EPR spectroscopy this time is around 10 ns [41].…”
Section: Dimeric Assemblies Of {Cr 7 Ni} Wheels As Double Qubit-basedmentioning
confidence: 99%
“…These are characterized by a S = 1/2 ground state, and coherence times above 10 µs have been demonstrated on properly engineered variants [12]. Rabi oscillations within the computational doublet (corresponding to single-qubit gates) have already been performed on ensembles of MNMs [13][14][15], as well as two-qubit operations in dimers of permanently coupled molecular qubits [16,17]. However, an important and much more challenging step towards the realization of a digital quantum simulator is the physical implementation of two-qubit entangling gates on a scalable architecture.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Quantifying weak interactions between very different spins is challenging.I n cases where the interaction can easily be measured, for example by magnetometry or continuous-wave (CW) electron paramagnetic resonance (EPR) spectroscopy, [8] the interaction will be too large to permit implementation of both one-and two-qubit gates in the same molecule. [3] CW EPR spectroscopy can still be au seful tool to investigate dipolar interactions;byobserving the line broadening of aN triplet in at wo-qubit structure,Z hou et al showed the existence of ad ipolar interaction that they could estimate in conjunction with spin density calculations. [9] On the other hand, DEER spectroscopy, [10] while ap owerful tool to measure weak interactions by directly manipulating two weakly interacting spins with specific microwave pulses,i s limited as the bandwidth of the microwave source must encompass the resonant frequency of both electron spins.…”
mentioning
confidence: 99%
“…This magnetic interaction would give agate time of 125 ns, which falls in the correct range to implement atwo-qubit gate with 1. [3] Unfortunately,w hile RIDME is very good at measuring the interaction between different spins it only addresses one of the two spins.T herefore,i fh eterospin systems were to be used in quantum algorithms there remains an eed for EPR spectrometers capable of pulsing at two distinct frequencies.…”
mentioning
confidence: 99%
See 1 more Smart Citation